Ultraviolet-proof film and preparation method and application thereof

By using amino acid ionic liquid templates in PVC resin films to synthesize loaded zinc oxide powders and combining them with diatomaceous earth, the problem of insufficient UV resistance performance of existing PVC resin films is solved, and efficient UV resistance and oxidation resistance is achieved and wear resistance.

CN119463382APending Publication Date: 2025-02-18GUANGZHOU KAWEI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411679354.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing PVC resin films have weak UV resistance, which leads to the car paint and interior being easily damaged by ultraviolet rays when exposed to sunlight for a long time, which accelerates the aging process.

Method used

By using amino acid-based ionic liquids as templates, the supported zinc oxide powder was synthesized by solvothermal method and combined with a diatomaceous earth carrier to enhance its dispersion and stability in the polyvinyl chloride resin to form an ultraviolet-proof film.

Benefits of technology

It achieves excellent UV resistance, good oxidation resistance, wear resistance and visible light transmittance of the film, extending the service life of the product and improving the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147901180000141
    Figure BDA0005147901180000141
Patent Text Reader

Abstract

The invention relates to the field of films, in particular to an anti-ultraviolet film and a preparation method and application thereof. The invention discloses an ultraviolet-proof film which is prepared from the following raw materials in parts by weight: 50-60 parts of polyvinyl chloride resin, 1-2 parts of an antioxidant, 5-8 parts of a coupling agent and 2-4 parts of supported zinc oxide powder. According to the ultraviolet-proof film, amino acid ionic liquid is used as a template, supported zinc oxide powder is synthesized through a solvothermal method, the powder is combined with a diatomite loading agent to prevent agglomeration, and the dispersity and stability of the powder in polyvinyl chloride resin are enhanced; then, mixing the supported zinc oxide powder, an antioxidant and a coupling agent in polyvinyl chloride resin according to a specific weight part ratio, forming a film through a tape casting method, curing and drying, and finally preparing the film with excellent ultraviolet-proof performance, good oxidation resistance, wear resistance and visible light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of films, and in particular to an anti-ultraviolet film and a preparation method and application thereof. Background Art

[0002] PVC resin film, as a plastic material widely used in packaging, construction, automobiles and other fields, has made significant progress in technology development and application expansion in recent years. Especially in the field of car covers, PVC resin film has become the preferred protective material for many car owners due to its advantages such as wear resistance, acid and alkali resistance, and good processing performance.

[0003] At present, the production technology of PVC resin film is relatively mature, and it is able to produce film products with different thicknesses, colors and functions. At the same time, with the enhancement of environmental awareness, more and more companies have begun to pay attention to the environmental performance of PVC resin film and are committed to developing low-toxic and low-pollution production processes and products. In addition, in terms of processing technology, the molding, printing, and lamination processes of PVC resin film have also been continuously improved and perfected, improving product quality and production efficiency.

[0004] However, the current PVC resin film has relatively weak anti-ultraviolet performance, which makes the car paint and interior easily damaged by ultraviolet rays when the car cover film is exposed to sunlight for a long time, accelerating the aging process; in addition, the problem that PVC resin film is easy to deform at high temperatures also limits its application in the car cover field.

[0005] To this end, the present application provides an anti-ultraviolet film and a preparation method and application thereof. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present application provides an anti-ultraviolet film and a preparation method and application thereof. The anti-ultraviolet film uses an amino acid ionic liquid as a template and synthesizes a supported zinc oxide powder by a solvent thermal method. The powder is combined with a diatomaceous earth support agent to prevent agglomeration, thereby enhancing its dispersibility and stability in a polyvinyl chloride resin. Then, the supported zinc oxide powder is mixed with an antioxidant and a coupling agent in a polyvinyl chloride resin in a specific weight ratio, and a film is formed by a casting method and cured and dried to finally prepare a film with excellent anti-ultraviolet performance, good oxidation resistance, wear resistance and visible light transmittance.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] In a first aspect, the present application provides an anti-ultraviolet film, which comprises the following raw materials in parts by weight:

[0009] 50-60 parts of polyvinyl chloride resin, 1-2 parts of antioxidant, 5-8 parts of coupling agent, 2-4 parts of supported zinc oxide powder;

[0010] (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring;

[0011] (2) Under stirring conditions, using sodium hydroxide solution to adjust the solution pH to 12, and then performing a first reaction. After the first reaction is completed, a loading agent is added to perform a second reaction;

[0012] (3) After the second reaction is completed, the mixed solution after the reaction is centrifuged and washed, and then dried to obtain supported zinc oxide powder.

[0013] Specifically, in the present application, zinc oxide is synthesized by a solvothermal method using an amino acid ionic liquid tetramethylammonium glycine [N 1111 [Gly] as a template), zinc acetate as a zinc source, in a mixed solvent of ethanol and deionized water, by heating to above the boiling point of the solvent, a high temperature and high pressure reaction environment is created, which causes the zinc source to decompose and release zinc ions, and these zinc ions react with hydroxyl ions in the solvent to form zinc oxide crystals, while the ionic liquid template helps to control the nucleation and growth process of the zinc oxide crystals, thereby synthesizing a nanostructured zinc oxide powder;

[0014] Nanostructured zinc oxide powder may be easily agglomerated during use due to its small particle size, resulting in a decrease in its ability to shield ultraviolet rays. In order to prevent the agglomeration of the nanostructured zinc oxide powder and allow the nanostructured zinc oxide powder to better shield ultraviolet rays, the present invention loads the nanostructured zinc oxide powder on the loading agent by adding a loading agent, thereby obtaining a loaded zinc oxide powder that is not easy to agglomerate and has strong ultraviolet shielding and has improved wear resistance to a certain extent.

[0015] In some specific embodiments, the polyvinyl chloride resin is SG-5 type polyvinyl chloride resin.

[0016] In some specific embodiments, the antioxidant is an aromatic amine antioxidant.

[0017] Specifically, in the present application, aromatic amine antioxidants can effectively capture and neutralize free radicals, thereby slowing down the oxidative degradation process of the film, improving the antioxidant properties of the UV-proof film, and preventing the film from aging and yellowing due to oxidation during use.

[0018] In some specific embodiments, the coupling agent includes any one of γ-aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane.

[0019] Specifically, in the present application, the silanol group of the coupling agent can react with the hydroxyl group on the surface of the inorganic filler to form a covalent bond, and at the same time, its amino group or hydrocarbon group can form a coordination bond or a hydrogen bond with the chlorine atom in the polyvinyl chloride resin, thereby establishing a chemical bond between the inorganic filler and the organic resin; the long hydrocarbon chain of the coupling agent can be physically entangled between the polymer chains, increasing the degree of entanglement at the interface, thereby improving the bonding strength of the interface.

[0020] Moreover, the introduction of coupling agents can reduce the aggregation between filler particles and improve the dispersion of fillers in resin, thereby increasing the contact area between fillers and resins and improving the interfacial bonding force. In addition, coupling agents can reduce the interfacial tension between inorganic fillers and polyvinyl chloride resins, making it easier for resins to wet fillers and increase the contact area between the two; at the same time, coupling agents can serve as a bridge for stress transfer, transferring stress from resins to fillers and improving the overall mechanical strength of the material.

[0021] In some embodiments, the supporting agent is diatomaceous earth.

[0022] Specifically, diatomite, as a loading agent, can load the nanostructured zinc oxide powder on it, effectively preventing the zinc oxide powder from agglomerating; by adding diatomite, the dispersion and stability of the zinc oxide powder in the anti-ultraviolet film can be improved, so that it can better play the role of shielding ultraviolet rays. Moreover, the addition of diatomite can also help improve the wear resistance of the film, making the anti-ultraviolet film more durable during use.

[0023] In some specific embodiments, the weight ratio of the amino acid ionic liquid, zinc acetate, and the loading agent is 3-4:20:40.

[0024] In some specific embodiments, the first reaction is carried out at 1-2 MPa and 120-140° C. for 24-28 h; the second reaction is carried out at 60-70° C. for 12-16 h.

[0025] In a second aspect, the present application provides a method for preparing an anti-ultraviolet film, comprising the following steps:

[0026] S1. Preparation of supported zinc oxide powder

[0027] (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring;

[0028] (2) Under stirring conditions, using sodium hydroxide solution to adjust the solution pH to 12, and then performing a first reaction. After the first reaction is completed, a loading agent is added to perform a second reaction;

[0029] (3) After the second reaction is completed, the mixed solution after the reaction is centrifuged and washed, and then dried to obtain a supported zinc oxide powder;

[0030] S2. Preparation of film-forming liquid

[0031] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution, stir evenly and disperse by ultrasonic to obtain a suspension A;

[0032] Then, the antioxidant, coupling agent and supported zinc oxide powder are slowly poured into the N,N-dimethylformamide solution, stirred evenly and dispersed by ultrasonication to obtain a suspension B;

[0033] Slowly drip suspension B into suspension A and continue stirring for 3-4 hours to obtain a uniform film-forming liquid;

[0034] S3. Film forming by tape casting

[0035] The film-forming liquid is evenly coated on a glass plate by a casting method and waited for solidification; after solidification, it is placed in a vacuum drying oven for drying and peeling treatment to obtain an anti-ultraviolet film.

[0036] In some specific embodiments, in step S3, the drying is performed at 60° C. for 24-30 hours.

[0037] In a third aspect, the present application provides an application of an anti-ultraviolet film, wherein the anti-ultraviolet film described in the first aspect or the second aspect is applied to a car cover.

[0038] The beneficial effects of the present invention are:

[0039] In the present application, the film effectively improves the UV protection performance of the film through a specific raw material ratio and preparation process, and at the same time has good antioxidant properties, wear resistance and visible light transmittance, and can be widely used in car covers and other fields, effectively extending the service life of the product and improving the overall performance of the product. DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0041] In the embodiments and comparative examples, the specific sources of some raw materials are as follows:

[0042] The polyvinyl chloride resin is SG-5 type polyvinyl chloride resin.

[0043] The amino acid ionic liquid is the amino acid ionic liquid tetramethylammonium glycine [N 1111][Gly], specifically, can be obtained commercially or prepared according to the preparation method described in "Study on the performance of [N1111][Gly] composite working fluid for CO2 absorption / desorption" by Liu Zhonghai, 2014; specifically, in the process of solvothermal synthesis of supported zinc oxide powder, amino acid ionic liquid is used as a template to help control the nucleation and growth process of zinc oxide crystals; the glycine part can form a coordination bond with zinc ions to guide the growth direction and morphology of zinc oxide crystals; the long-chain alkyl part of the ionic liquid helps prevent the agglomeration of nanoparticles, thereby obtaining uniformly dispersed nanostructured zinc oxide powder. Moreover, the amphiphilic nature of the ionic liquid helps to improve the dispersibility of zinc oxide powder in polyvinyl chloride resin, thereby enhancing the performance of the film.

[0044] Aromatic amine antioxidant, using antioxidant 445, chemical name is 4,4'-bis (α, α-dimethylbenzyl) diphenylamine, CAS number is 10081-67-1.

[0045] Example 1

[0046] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0047] 50 parts of polyvinyl chloride resin, 1 part of aromatic amine antioxidant, 5 parts of γ-aminopropyltriethoxysilane, and 2 parts of supported zinc oxide powder;

[0048] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0049] S1. Preparation of supported zinc oxide powder

[0050] (1) In a pressure autoclave, add an amino acid ionic liquid and zinc acetate, then add them to an ethanol-water mixed solution, and mix them thoroughly under stirring;

[0051] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 120° C. for 24 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 60° C. for 12 h to carry out the second reaction;

[0052] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0053] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 3:20:40:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0054] S2. Preparation of film-forming liquid

[0055] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0056] Then, the antioxidant, coupling agent and supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times of the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0057] Slowly drop suspension B into suspension A and continue stirring for 3 hours to obtain a uniform film-forming liquid;

[0058] S3. Film forming by tape casting

[0059] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 24 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0060] Example 2

[0061] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0062] 60 parts of polyvinyl chloride resin, 2 parts of aromatic amine antioxidant, 8 parts of γ-aminopropyltriethoxysilane, and 4 parts of supported zinc oxide powder;

[0063] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0064] S1. Preparation of supported zinc oxide powder

[0065] (1) In a pressure autoclave, add an amino acid ionic liquid and zinc acetate, then add them to an ethanol-water mixed solution, and mix them thoroughly under stirring;

[0066] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 140° C. for 28 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 70° C. for 16 h to carry out the second reaction;

[0067] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0068] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 4:20:40:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0069] S2. Preparation of film-forming liquid

[0070] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0071] Then, the antioxidant, coupling agent and supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times of the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0072] Slowly drip suspension B into suspension A and continue stirring for 3-4 hours to obtain a uniform film-forming liquid;

[0073] S3. Film forming by tape casting

[0074] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 30 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0075] Example 3

[0076] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0077] 55 parts of polyvinyl chloride resin, 1.5 parts of aromatic amine antioxidant, 6 parts of γ-aminopropyltriethoxysilane, and 3 parts of supported zinc oxide powder;

[0078] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0079] S1. Preparation of supported zinc oxide powder

[0080] (1) In a pressure autoclave, add an amino acid ionic liquid and zinc acetate, then add them to an ethanol-water mixed solution, and mix them thoroughly under stirring;

[0081] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 130° C. for 26 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 65° C. for 14 h to carry out the second reaction;

[0082] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0083] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 3.5:20:40:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0084] S2. Preparation of film-forming liquid

[0085] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0086] Then, the antioxidant, coupling agent and supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times of the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0087] Slowly drop suspension B into suspension A and continue stirring for 3.5 hours to obtain a uniform film-forming liquid;

[0088] S3. Film forming by tape casting

[0089] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 28 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0090] Example 4

[0091] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0092] 52 parts of polyvinyl chloride resin, 1.3 parts of aromatic amine antioxidant, 6 parts of γ-aminopropyltrimethoxysilane, and 2.5 parts of supported zinc oxide powder;

[0093] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0094] S1. Preparation of supported zinc oxide powder

[0095] (1) In a pressure autoclave, add an amino acid ionic liquid and zinc acetate, then add them to an ethanol-water mixed solution, and mix them thoroughly under stirring;

[0096] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 125° C. for 25 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 60° C. for 16 h to carry out the second reaction;

[0097] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0098] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 3.2:20:40:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0099] S2. Preparation of film-forming liquid

[0100] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0101] Then, the antioxidant, coupling agent and supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times of the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0102] Slowly drop suspension B into suspension A and continue stirring for 3.5 hours to obtain a uniform film-forming liquid;

[0103] S3. Film forming by tape casting

[0104] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 26 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0105] Example 5

[0106] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0107] 58 parts of polyvinyl chloride resin, 1.8 parts of aromatic amine antioxidant, 7 parts of γ-aminopropyltrimethoxysilane, and 3.5 parts of supported zinc oxide powder;

[0108] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0109] S1. Preparation of supported zinc oxide powder

[0110] (1) In a pressure autoclave, add an amino acid ionic liquid and zinc acetate, then add them to an ethanol-water mixed solution, and mix them thoroughly under stirring;

[0111] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 130° C. for 27 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 70° C. for 12 h to carry out the second reaction;

[0112] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0113] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 3.8:20:40:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0114] S2. Preparation of film-forming liquid

[0115] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0116] Then, the antioxidant, coupling agent and supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times of the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0117] Slowly drip suspension B into suspension A and continue stirring for 3-4 hours to obtain a uniform film-forming liquid;

[0118] S3. Film forming by tape casting

[0119] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 27 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0120] Comparative Example 1

[0121] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0122] 50 parts of polyvinyl chloride resin;

[0123] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0124] S2. Preparation of film-forming liquid

[0125] Slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution is 10 times that of the polyvinyl chloride resin), stir evenly and perform ultrasonic dispersion for 50 minutes to obtain a suspension A;

[0126] S3. Film forming by tape casting

[0127] Use the casting method to evenly coat the suspension A on the glass plate and wait for solidification; after solidification, put it into a vacuum drying oven at 60°C for 24 hours; after cooling, put it into deionized water to allow the film to fall off naturally, and obtain an anti-ultraviolet film with a thickness of about 50 (±5) μm.

[0128] Comparative Example 2

[0129] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0130] 50 parts of polyvinyl chloride resin, 1 part of aromatic amine antioxidant, 5 parts of γ-aminopropyltriethoxysilane, and 2 parts of zinc oxide powder;

[0131] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0132] S1. Preparation of zinc oxide powder

[0133] (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring;

[0134] (2) Under stirring conditions, the solution pH is adjusted to 12 using sodium hydroxide solution, and then the pressure is controlled at 1-2 MPa and the temperature is 120° C. for 24 hours to carry out the first reaction;

[0135] (3) After the first reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain zinc oxide powder;

[0136] The weight ratio of amino acid ionic liquid, zinc acetate and ethanol-water mixed solution is 3:20:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0137] S2. Preparation of film-forming liquid

[0138] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0139] Then, the antioxidant, coupling agent and zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times that of the zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0140] Slowly drop suspension B into suspension A and continue stirring for 3 hours to obtain a uniform film-forming liquid;

[0141] S3. Film forming by tape casting

[0142] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 24 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0143] Comparative Example 3

[0144] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0145] 50 parts of polyvinyl chloride resin, 1 part of aromatic amine antioxidant, 5 parts of γ-aminopropyltriethoxysilane, and 2 parts of supported zinc oxide powder;

[0146] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0147] S1. Preparation of supported zinc oxide powder

[0148] (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring;

[0149] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 120° C. for 24 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 60° C. for 12 h to carry out the second reaction;

[0150] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0151] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 3:20:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0152] S2. Preparation of film-forming liquid

[0153] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0154] Then, the antioxidant, coupling agent and supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times of the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0155] Slowly drop suspension B into suspension A and continue stirring for 3 hours to obtain a uniform film-forming liquid;

[0156] S3. Film forming by tape casting

[0157] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 24 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0158] Comparative Example 4

[0159] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0160] 50 parts of polyvinyl chloride resin, 1 part of aromatic amine antioxidant, 2 parts of supported zinc oxide powder;

[0161] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0162] S1. Preparation of supported zinc oxide powder

[0163] (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring;

[0164] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 120° C. for 24 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 60° C. for 12 h to carry out the second reaction;

[0165] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0166] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 3:20:40:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0167] S2. Preparation of film-forming liquid

[0168] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0169] Then, the antioxidant and the supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0170] Slowly drop suspension B into suspension A and continue stirring for 3 hours to obtain a uniform film-forming liquid;

[0171] S3. Film forming by tape casting

[0172] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 24 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0173] Comparative Example 5

[0174] An anti-ultraviolet film comprises the following raw materials in parts by weight:

[0175] 50 parts of polyvinyl chloride resin, 5 parts of γ-aminopropyltriethoxysilane, and 2 parts of supported zinc oxide powder;

[0176] The method for preparing the above-mentioned anti-ultraviolet film comprises the following steps:

[0177] S1. Preparation of supported zinc oxide powder

[0178] (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring;

[0179] (2) Under stirring conditions, sodium hydroxide solution was used to adjust the solution pH to 12, and then the pressure was controlled at 1-2 MPa and the temperature was 120° C. for 24 h to carry out the first reaction. After the first reaction, a supporting agent (diatomaceous earth) was added and the reaction was carried out at 60° C. for 12 h to carry out the second reaction;

[0180] (3) After the second reaction is completed, the reaction mixture is centrifuged and washed, and dried at 60° C. for 30 h to obtain supported zinc oxide powder;

[0181] The weight ratio of amino acid ionic liquid, zinc acetate, loading agent and ethanol-water mixed solution is 3:20:40:600; the weight content of ethanol in the ethanol-water mixed solution is 10%, and the mass concentration of sodium hydroxide solution is 30%.

[0182] S2. Preparation of film-forming liquid

[0183] Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution (the N,N-dimethylformamide solution is 10 times the weight of the polyvinyl chloride resin), stir evenly and ultrasonically disperse for 50 minutes to obtain a suspension A;

[0184] Then, the coupling agent and the supported zinc oxide powder were slowly poured into the N,N-dimethylformamide solution (the weight of the N,N-dimethylformamide solution was 15 times the weight of the supported zinc oxide powder), stirred evenly and ultrasonically dispersed for 50 minutes to obtain a suspension B;

[0185] Slowly drop suspension B into suspension A and continue stirring for 3 hours to obtain a uniform film-forming liquid;

[0186] S3. Film forming by tape casting

[0187] The film-forming liquid was evenly coated on the glass plate by the casting method and waited for solidification; after solidification, it was placed in a vacuum drying oven at 60°C for 24 hours; after cooling, it was placed in deionized water to allow the film to fall off naturally, and an anti-ultraviolet film with a thickness of about 50 (±5) μm was obtained.

[0188] Performance Testing

[0189] The films prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to the following performance tests:

[0190] 1. Visible light transmittance test

[0191] Taking ASTM D1003 as the reference standard, the percentage of visible light with a wavelength range of 380 to 780 nm passing through the sample surface is detected;

[0192] 2. UV transmittance test

[0193] Use a UV spectrophotometer to test the absorbance of the sample in the wavelength range of 300 to 420 nm.

[0194] 3. Color difference △E

[0195] The initial Lab value of the product was tested using a colorimeter according to the CIE 2000 test standard. The product was then placed in an 80°C oven at normal pressure and temperature for 300 hours and then taken out. The Lab value of the product was tested using the same method, and the color difference △E before and after aging was calculated using the Lab values ​​before and after placement.

[0196] 4. Wear resistance

[0197] The force required to scratch the film was measured using an Erichsen scratch tester (ISO 4586-2 / DINEN 438-2) with a 0.5 mm tip.

[0198] The above test results are summarized in Table 1 below.

[0199] Table 1

[0200]

[0201] It can be seen from Table 1 that, for example, the film prepared in Example 1 has good UV protection performance (UV transmittance 1.85%), while maintaining a high visible light transmittance (75%) and a certain abrasion resistance (12.9N). In addition, the color difference ΔE is small (0.71), indicating that the color of the film is close to the standard or expected color and has excellent yellowing resistance.

[0202] In Comparative Example 1, after only PVC resin was used to form a film, the UV transmittance was high and the color difference ΔE reached 40.5, indicating that the UV protection effect was poor and the yellowing resistance effect was relatively poor, and the wear resistance was low.

[0203] The film prepared in Comparative Example 2 (without adding a loading agent) has a visible light transmittance of 76%, a UV transmittance of 20.8%, a color difference (△E) of 5.8, and a wear resistance of 9.8N. It can be seen that after not using a loading agent for loading, the UV transmittance increased significantly, the UV protection function decreased, and the wear resistance also decreased significantly.

[0204] The film prepared in Comparative Example 3 (zinc oxide prepared without adding heat sealing reaction) has a visible light transmittance of 78%, an ultraviolet transmittance of 55.3%, a color difference (△E) of 1.2, and a wear resistance of 11.1N. It can be seen that when zinc oxide is prepared without adding heat sealing reaction, the ultraviolet transmittance is significantly increased and the ultraviolet protection function is reduced.

[0205] The film prepared in Comparative Example 4 (without adding coupling agent) has a visible light transmittance of 75%, an ultraviolet transmittance of 10.4%, a color difference (△E) of 8.6, and an abrasion resistance of 11.6N. It can be seen that after not adding coupling agent, the ultraviolet transmittance increases, the anti-ultraviolet function decreases, and the color difference increases.

[0206] The film prepared in Comparative Example 5 (without adding aromatic amine antioxidants) has a visible light transmittance of 75%, an ultraviolet transmittance of 1.95%, a color difference (△E) of 38.9, and an abrasion resistance of 12.8N. It can be seen that the color difference is significantly increased after no aromatic amine antioxidants are added.

[0207] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. An anti-ultraviolet film, characterized in that: In parts by weight, it includes the following raw materials: 50-60 parts of polyvinyl chloride resin, 1-2 parts of antioxidant, 5-8 parts of coupling agent, 2-4 parts of supported zinc oxide powder; The preparation method of the supported zinc oxide powder comprises the following steps: (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring; (2) Under stirring conditions, using sodium hydroxide solution to adjust the solution pH to 12, and then performing a first reaction. After the first reaction is completed, a loading agent is added to perform a second reaction; (3) After the second reaction is completed, the mixed solution after the reaction is centrifuged and washed, and then dried to obtain supported zinc oxide powder.

2. The anti-ultraviolet film according to claim 1, characterized in that: The polyvinyl chloride resin is SG-5 type polyvinyl chloride resin.

3. The anti-ultraviolet film according to claim 1, characterized in that: The antioxidant is an aromatic amine antioxidant.

4. The anti-ultraviolet film according to claim 1, characterized in that: The coupling agent includes any one of γ-aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane.

5. The anti-ultraviolet film according to claim 1, characterized in that: The supporting agent is diatomaceous earth.

6. The anti-ultraviolet film according to claim 1, characterized in that: The weight ratio of the amino acid ionic liquid, zinc acetate and the loading agent is 3-4:20:

40.

7. The anti-ultraviolet film according to claim 1, characterized in that: The conditions for the first reaction are 1-2 MPa and 120-140° C. for 24-28 h; the conditions for the second reaction are 60-70° C. for 12-16 h.

8. The method for preparing the anti-ultraviolet film according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Preparation of supported zinc oxide powder (1) Weighing an amino acid ionic liquid and zinc acetate, adding them to an ethanol-water mixed solution in sequence, and mixing them thoroughly under stirring; (2) Under stirring conditions, using sodium hydroxide solution to adjust the solution pH to 12, and then performing a first reaction. After the first reaction is completed, a loading agent is added to perform a second reaction; (3) After the second reaction is completed, the mixed solution after the reaction is centrifuged and washed, and then dried to obtain a supported zinc oxide powder; S2. Preparation of film-forming liquid Prepare the corresponding raw materials according to the weight composition of the anti-ultraviolet film; slowly pour the polyvinyl chloride resin into the N,N-dimethylformamide solution, stir evenly and disperse by ultrasonic to obtain a suspension A; Then, the antioxidant, coupling agent and supported zinc oxide powder are slowly poured into the N,N-dimethylformamide solution, stirred evenly and dispersed by ultrasonication to obtain a suspension B; Slowly drip suspension B into suspension A and continue stirring for 3-4 hours to obtain a uniform film-forming liquid; S3. Film forming by tape casting The film-forming liquid is evenly coated on a glass plate by a casting method and waited for solidification; after solidification, it is placed in a vacuum drying oven for drying and peeling treatment to obtain an anti-ultraviolet film.

9. The preparation method according to claim 8, characterized in that: In step S3, the drying is performed at 60° C. for 24-30 hours.

10. An application of an anti-ultraviolet film, characterized in that: The anti-ultraviolet film according to any one of claims 1 to 7 or the anti-ultraviolet film prepared by the preparation method according to any one of claims 8 to 9 is applied to car covers.